До питання виділення фонем у мовному сигналі за допомогою ефекту стоячої хвилі - Безвербний, І.А. (Комп’ютерні засоби, мережі та системи, 2019)
Завданням цієї роботи є вироблення нового адаптивного методу, спираючись на розроблений раніше алгоритм виділення фонем у мовному сигналі. Особливістю нового методу є скорочення кількості обчислень завдяки використанню ефекту стоячої хвилі. Задача этой работы - создание нового адаптивного метода на основе ранее разработанного алгоритма выделения фонем в речевом сигнале. Особенность нового метода в сокращении количества вычислений благодаря использованию эффекта стоячей волны. The task of this work is to develop a new adaptive method, based on the algorithm for the allocation of phonemes in the speech signal developed earlier A feature of the new method is to reduce the number of computations by using a standing wave effect to identify individual phonemes in recognition. The article presents an adaptive method of segmentation of speech signals using the standing wave effect, which is constructed using the Hilbert - Huang transform principles and the method of empirical mode decomposition.